Prevalence of loneliness and its associated factors among elderly attending primary health clinics in Kuantan, Pahang. - Md Aris, Mohd Aznan; Abu Bakar, Anifah; Abdullah, Fa’iza; Mohd Rus, Razman (2021)
Introduction: Loneliness is very common in late stages of life. Previous studies showed that loneliness is associated with depression, sleep problems and suicidal ideation. There is limited data and studies regarding loneliness among elderly in Malaysia. The aim of this study was to measure the prevalence of loneliness and its associated factors among elderly attending primary health clinics in Kuantan, Pahang. Materials and Methods: A cross sectional study was conducted in 4 selected primary health clinics in Kuantan. A total of 350 elderly aged 60 years and above were recruited. The data were collected by an interviewer administered questionnaire. A validated Malay version of 6-Item De Jong Gierveld Loneliness Scale was used to measure loneliness. Descriptive statistics were used to measure the prevalence and logistic regression to identify factors associated with loneliness among elderly. Data were analysed using SPSS version 25.0. Results: About 97.1% were elderly and 2.9% were oldest old. Majority were female (69.1%), Malay (77.1%), married (62%), have at least 1 child (94.9%) and lives with children (65.1%). The prevalence of loneliness among elderly attending primary health clinics in Kuantan is 48%. This study showed that the oldest old (AOR: 9.099 CI: 1.086-76.237) and being single/widowed/divorced/separated (AOR 2.33 CI: 1.426-3.81) were significantly associated with loneliness, while co-residence with children is a protective factor for loneliness (AOR: 0.552 CI: 0.335-0.909). Conclusion: Loneliness is a modifiable health risk. Therefore, it is important to identify loneliness among elderly and intervene early